2001
DOI: 10.1590/s0004-27492001000100008
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos médicos e sociais no atendimento oftalmológico de urgência

Abstract: Aspectos médicos e sociais no atendimento oftalmológico de urgência

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
18
1
6

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 5 publications
3
18
1
6
Order By: Relevance
“…A research conducted in the ER of UNICAMP, reported that 87.5% of the patients coming from other services were unnecessarily referred to specialized reference centers and/or came by their own initiative to check the treatment, which shows little confidence in the first service (15) . In Brazil, researchers (16) found that 32.0% of patients in the ophthalmologic sector were searching for a second opinion, being the main reasons of this management: confirmation of the diagnostic (43.0%); lack of confidence in the first doctor (33.0%) and perception of lack of interest from the professionals (24.0%).…”
Section: Discussionmentioning
confidence: 99%
“…A research conducted in the ER of UNICAMP, reported that 87.5% of the patients coming from other services were unnecessarily referred to specialized reference centers and/or came by their own initiative to check the treatment, which shows little confidence in the first service (15) . In Brazil, researchers (16) found that 32.0% of patients in the ophthalmologic sector were searching for a second opinion, being the main reasons of this management: confirmation of the diagnostic (43.0%); lack of confidence in the first doctor (33.0%) and perception of lack of interest from the professionals (24.0%).…”
Section: Discussionmentioning
confidence: 99%
“…Veracity of the emergency was categorized as ''true'' or ''not-true" emergency. A true ocular emergency was considered if there were risk of decreasing or loss vision, as well as cases requiring immediate (same day) evaluation in either an emergency department or an ophthalmology outpatient department due the intensity of symptoms (1) . The eye examination consisted of visual acuity using a Snellen chart, anterior segment examination by slit lamp, intraocular pressure measured with a Goldmann tonometer (except children aged five years or younger), and, if possible, given the condition of the eye, a posterior segment examination after pupil dilatation.…”
Section: Methodsmentioning
confidence: 99%
“…Some tend towards self-medication or simply to request drugs in the drugstore, while others ask for general practitioner or ophthalmology consultations (1,2) . Emergency areas have traditionally provided care to anyone requesting it, including patients with non-urgent complaints.…”
mentioning
confidence: 99%
See 2 more Smart Citations